2020
DOI: 10.1182/hematology.2020000157
|View full text |Cite
|
Sign up to set email alerts
|

How do we sequence therapy for marginal zone lymphomas?

Abstract: Marginal zone lymphomas are indolent diseases. Overall survival rates are very good, but patients tend to relapse and may do so several times. The concept of treatment sequencing is therefore important and necessary to preserve adequate organ function and to avoid excessive toxicity, with the final goal of achieving long survival times. Systemic treatments and chemotherapy are considered to be an option in multiply relapsing disease, in cases that are in an advanced stage at presentation or relapse, and in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Exposure to such effective therapies needs a powerful prognostic tool for sequencing of available therapies to avoid excessive toxicity. 21 In our study, Ig paraproteinaemia together with MALT-IPI was shown to improve our ability to identify high-risk populations, which is critically important in therapeutic management.…”
Section: Discussionmentioning
confidence: 77%
“…Exposure to such effective therapies needs a powerful prognostic tool for sequencing of available therapies to avoid excessive toxicity. 21 In our study, Ig paraproteinaemia together with MALT-IPI was shown to improve our ability to identify high-risk populations, which is critically important in therapeutic management.…”
Section: Discussionmentioning
confidence: 77%
“…The median PFS and DOR were 12 and 10 months, respectively [ 86 ]. As seen with other therapeutic advances, dedicated analyses of this indolent subtype are made difficult by their relatively rarity and insights are largely extrapolated from broader cohorts of B cell malignancies [ 104 ].…”
Section: Efficacy Of Venetoclax In Other B Cell Neoplasmsmentioning
confidence: 99%
“…Systemic therapy is often prescribed in localized patients who cannot tolerate the adverse effects of radiotherapy, or in those with advanced or disseminated MALT lymphoma [ 10 , 20 , 21 , 23 , 105 ]. Previously, several phase II studies evaluating new purine analogs of chemotherapy agents, such as fludarabine and 2CdA, provided approximately 50% ORRs, but these drugs caused myelosuppression [ 10 , 20 , 21 , 23 , 105 , 106 ].…”
Section: Clinical Efficacy Of Immunomodulatory Agents For Hp-negative...mentioning
confidence: 99%
“…Systemic therapy is often prescribed in localized patients who cannot tolerate the adverse effects of radiotherapy, or in those with advanced or disseminated MALT lymphoma [ 10 , 20 , 21 , 23 , 105 ]. Previously, several phase II studies evaluating new purine analogs of chemotherapy agents, such as fludarabine and 2CdA, provided approximately 50% ORRs, but these drugs caused myelosuppression [ 10 , 20 , 21 , 23 , 105 , 106 ]. In a randomized International Extranodal Lymphoma Study Group (IELSG)-19 trial comparing chlorambucil, rituximab, and combined chlorambucil and rituximab as first-line treatments for patients with MALT lymphoma, Zucca et al showed that the ORR for chlorambucil, rituximab, and combined chlorambucil and rituximab arms were 85.5%, 78.3%, and 94.7%, respectively [ 107 ].…”
Section: Clinical Efficacy Of Immunomodulatory Agents For Hp-negative...mentioning
confidence: 99%
See 1 more Smart Citation